(untitled) (E Conference Zone, 2022)
In this article, women’s rights are an integral and integral part of human rights and are reflected in special international and national documents, taking into account the sexual and other characteristics of women. Women’s rights are indivisible, and they include all civil, political, social, economic, and cultural rights, as well as individual rights.